The rising prominence of John Owen: A research article of “The Ashgate Research Companion to John Owen’s Theology” - McGraw, Ryan (Nederduitse Gereformeerde Teologiese Tydskrif, 2015)
Scholars are only recently beginning to note the importance of John Owen as a seventeenth-century reformed orthodox theologian. The Ashgate Research Companion to John Owen’s Theology is the first book of its kind. This fact should flag this work as an important benchmark in Owen studies. Kelly Kapic and Mark Jones have assembled a wide array of scholars to treat aspects of Owen’s theology from the standpoint of his relevance both to historical theology and to contemporary reflection. While all of the essays in this volume will attract those interested in Owen and in the theological topics treated, they are not all of equal quality. This work is not only important for historical theology. It has the potential to bring Owen’s theology to bear on many areas of contemporary theology. Because of the importance of this book, each chapter merits careful analysis.